REASONS FOR SPATIAL ORIENTATION ILLUSIONS APPEARING DURING PLANE PILOTING - Грабовська, О.Ю. (Proceedings of National Aviation University (archive), 2012)
Various types of pilot’s spatial disorientation are described. Complicated and critical situations during the flight are defined that contribute to development of spatial orientation illusions. Moreover, attitude indicators and their imperfections are compared. It can be concluded on the basis of the carried out research that in order to prevent from appearing of spatial orientation illusions all factors which might influence the normal state of flight should be taken into account.